K-01 Agricultural exposures and health outcomes. (April 2019) - Freeman, Laura Beane
Abstract : Pesticides, including herbicides, insecticides, fungicides, fumigants and rodenticides, represent a diverse set of chemicals. They provide important benefits in public health, food production and aesthetics. However, unlike most other chemicals, pesticides are designed to impact living systems. Consequently there has long been a concern about the consequences on both human health and the environment. Pesticide use increased dramatically in the last half of the 20th century, with use continuing to increase in low and middle income countries, reflecting changing agricultural practices. Over 1 billion people are estimated to be exposed to pesticides occupationally through production, mixing, application and other tasks, particularly in the agricultural sector. But, these exposures can also experienced by the general population through various pathways, including drift and contamination of water and food supplies. Not surprisingly, given their diverse properties, various pesticides have been linked to a number of adverse health outcomes, including cancer, respiratory and neurologic disease and reproductive outcomes. With hundreds of pesticide active ingredients and changing practices over time, exposure assessment for etiologic research is a challenge, particularly for chronic diseases with potentially long latency. The ubiquity of the exposure and the concern about health risks by the general population make it imperative to study these important chemicals.